Synovial Chondromatosis of the Midcarpal Joint: A Case Report and Brief Review of Literature - PosthumaDeBoer, Jantine; Torrekens, Marieke; Nuffel, Maarten Van (Journal of Wrist Surgery, 2021)
Objective Synovial chondromatosis is a rare benign proliferative disorder of synovium characterized by the formation of cartilaginous bodies in a joint. The condition typically affects one single large joint. The development of synovial chondromatosis in the joints of hand and wrist is extremely rare.Case description In this report, we present a case of synovial chondromatosis arising from the midcarpal joint and the arthroscopic treatment thereof.Literature review Owing to its rarity, literature on synovial chondromatosis occurring in the hand and wrist is extremely limited. To our knowledge, no report has been published describing the arthroscopic treatment of an isolated synovial chondromatosis of the midcarpal joint.Clinical relevance As synovial chondromatosis of the hand and wrist is extremely rare, and clinical and radiological findings can be nonspecific, the diagnosis might be overlooked initially. The condition does, however, require surgical treatment and thorough follow-up. Thus, awareness of this possible diagnosis among treating physicians is important.
Keywords: wrist arthroscopy; synovial chondromatosis; imaging; histology